Effects of pH, temperature and competing ions on the adsorption of radiocesium on Prussian blue coated detonation nanodiamonds from aqueous solutions - Zaiger, Megan, author; Sudowe, Ralf, advisor; Johnson, Thomas, committee member; Lindsay, James, committee member (Colorado State University. Libraries, 2024)
The accident at the Fukushima Nuclear Powerplant, in 2011, resulted in the generation of radioactive contaminated water which is currently being stored on site. The Tokyo Electric Power Company (TEPCO), who owns the powerplant has begun treating and releasing the water into the ocean after most of the radioactivity has been removed by the Advanced Liquid Processing System (ALPS). Current techniques for preconcentration of radioisotopes, particularly radiocesium, from ocean waters are very labor and time intensive and often take months. Therefore, efficient, rapid, and reliable methods are needed for the determination of radiocesium in ocean water which represents a critical gap that this work seeks to address. A new technique using Prussian Blue (PB) coated detonation nanodiamonds (DND) to adsorb radiocesium from water samples is being investigated by the research group. The new technique takes hours to preconcentrate the radiocesium instead of months. The current study focuses on the effects of varying pH, temperature, competing ions, and stable cesium (Cs) on adsorption behavior of radiocesium. The results of the study show that high pH will result in a minimal decrease in Cs adsorption, while adsorption increases as pH increases, with the lowest adsorption of 95%. Temperature changes resulted in minimal decreases in Cs adsorption with the lowest adsorption of 98% measured at 4°C. Presence of potassium chloride (KCl), sodium chloride (NaCl), and lithium chloride (LiCl) at concentrations up to 1.0 M had no effect on the uptake of radiocesium showing adsorption of above 97% for all elements. However, adsorption decreased significantly in the presence of rubidium chloride (RbCl) as interferent concentration increased, with the lowest adsorption of 68% recorded for 1.0 M RbCl. The addition of stable Cs to low amounts of Cs-137 (1 Bq) saw high uncertainties and low adsorption reflecting the difficulty to obtain consistent results at very low concentrations. The study has shown promise for the use of DND in environmental settings with a continued need to be able to detect low levels of Cs-137.
Keywords: radiochemistry; health physics